Study of the current density of the electrical resistance sintering technique on microstructural and mechanical properties in a β Ti-Nb-Sn ternary alloy - Rossi, Mariana Correa; de Santi Gouvêa, Eber; Rodríguez, Montserrat Vicenta Haro; Saeki, Margarida Juri [UNESP]; Escuder, Angel Vicente; Borrás, Vicente Amigó (Springer Nature, 2021)
Electrical resistance sintering is a fast method to fabricate metallic samples in the metallurgy field and was used to obtain the Ti-Nb-Sn alloy to be applied as a possible biomaterial. Powders were obtained by mechanical alloying and were then compacted at 193 MPa pressure for 700 ms at several electrical current densities (11, 12 and 13 kA). The structure and microstructure of both powders and samples were evaluated by X-ray diffraction, Field Emission Scanning Electron Microscopy and Electron Backscattered Diffraction. Mechanical properties were evaluated by a microhardness assay and corrosion resistance was performed in Ringer Hartmann’s solution at 37°C. Samples were structured in the α, α” and β phases. The content of the β phase in the samples obtained at 11, 12 and 13 kA was 96.56, 98.12 and 98.02%, respectively. The peripheral zone showed more microporosity than the central zone. The microstructure was also formed by equiaxial bcc-β grains, and the samples obtained at 12 kA presented better microstructure homogeneity. Grain size increased as electric current density rose. The microhardness values fell within the 389–418 HV range and lowered, while electric current density increased. Corrosion tests proved the alloys’ excellent corrosion resistance (0.24–0.45 µA/cm2). The standard deviations of the kinetic parameters of the samples at 11 and 13 kA were much higher in relation to lack of microstructure homogeneity.
Keywords: Biomaterial; Corrosion resistance; ERS; Mechanical alloying; β-Ti alloy